Synthesis and characterization of alkyd resin based on palm fatty acid distillate (PFAD) modified with vegetable oil - Desi Nurandini; Lestari Hetalesi Saputri; Nopi Stiyati Prihatini (Jurnal Rekayasa Proses, 2026)
Coating industry is currently in urge to produce environmentally friendly products based on considerations of maintaining ecological stability. However, the coating industry, utilizing synthetic alkyd resins, generates substantial emissions of hazardous volatile organic solvent component, while its waste presents degradation challenges. Therefore, innovations are required to coating material from renewable and eco-friendly alkyd resins. Modifying alkyd resins with natural ingredients, such as vegetable oils and fatty acids, potentially enhances their performance as coating material. This research utilizes palm fatty acid distillate (PFAD), a byproduct of palm oil (CPO) processing, as a renewable material for alkyd resin. The use of vegetable oil to modify alkyd resin improves characteristics of the product. Drying-vegetable oil solidifies and hardens through a chemical reaction in which its components cross-link and form a tough, solid film due to oxidation upon exposure to the air. This research aims to study the synthesis process of PFAD-based alkyd resin modified with vegetable oil and investigate the effect of type and composition of modified oil on the characteristics of PFAD-based alkyd resin and its performance as coating material. In this research, PFAD, glycerol, and phthalic anhydride were reacted through a one-step polyesterification process (fatty acid process) at a temperature of 240°C for 4 hours. Modification was conducted by adding vegetable oil at various compositions (a comparison was carried out using several types of drying oil including candlenut oil, linseed oil, and tung oil). The alkyd resin product was characterized by determining its acid value, iodine value, and FTIR analysis, alongside evaluating its curing performance (drying speed) in application as a coating material. The best formulation for the characteristics qualified according to the Standar Nasional Indonesia (SNI 06-0504-1989) are alkyd resins with composition of 50% weight linseed oil (AR-LO-50) and composition of 50% weight tung oil (AR-TO-50) modification, i.e. acid value of 4.6 mgKOH/g sample and iodine number of 119.20 gI₂/100 g for linseed oil, then acid value of 8.31 mgKOH/g sample and iodine number of 102.44 gI₂/100 g for tung oil. The curing test results confirmed that the modified product meets the required 1-day drying time standard.